Cardiovascular Disease Risk Detection Through Cholesterol Examination - Ramayanti, Indri; Mayasari, Ni Made Elva; Rosita, Yanti; Prameswarie, Thia; Ghiffari, Ahmad; Suarni, Ertati; Indriyani, Indriyani; Oktariza, Rury Tiara; Erlyn, Putri; Anggina, Dientyah Nur; Zalika, Putri; Asmalia, Resy; Chairani, Liza (Indonesia Berdaya, 2022)
Cardiovascular disease is one of the world's most serious health issues, including in Indonesia. Early detection and screening for cardiovascular disease are beneficial in reducing disease-related mortality and morbidity. Unfortunately, in Indonesia, the general public (particularly the elderly) rarely undergoes early screening for cardiovascular disease. Most elderly people complain of neck heaviness, which is one of the symptoms of high cholesterol levels in the blood. However, the majority of them are unaware of this because they rarely and reluctantly have their blood tested at a health facility. The goal of this activity is to detect cardiovascular disease early by checking cholesterol levels for free and educating people about the importance of protecting one's health from the various diseases that it can cause. Physical examination (height, weight), vital sign examination (blood pressure, pulse), cholesterol examination, and education are the three rare screening programs. This activity was completed voluntarily by 43 people. The majority of the participants were women between the ages of 41 and 60. According to the total cholesterol test, the majority of the participants had total cholesterol levels greater than 200 mg/dl. This means that these individuals are at an increased risk of developing cardiovascular disease. Regular total cholesterol screening can help to prevent the development of cardiovascular disease and its complications, lowering cardiovascular disease mortality and morbidity in Indonesia.